2020
DOI: 10.1186/s12884-020-03172-8
|View full text |Cite
|
Sign up to set email alerts
|

Complicated COVID-19 in pregnancy: a case report with severe liver and coagulation dysfunction promptly improved by delivery

Abstract: Background: It has been proposed that pregnant women and their fetuses may be particularly at risk for poor outcomes due to the coronavirus (COVID-19) pandemic. From the few case series that are available in the literature, women with high risk pregnancies have been associated with higher morbidity. It has been suggested that pregnancy induced immune responses and cardio-vascular changes can exaggerate the course of the COVID-19 infection. Case presentation: A 26-year old Somalian woman (G2P1) presented with a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 23 publications
3
26
0
Order By: Relevance
“…The mother presented with classic COVID‐19 symptoms including fever and a dry cough, 26 but abdominal pain and reduced fetal movements were also reported. Similar to previous reports, we observed that the clinical condition of the mother improved rapidly after delivery 27,28 . The mother also presented with elevated concentrations of several acute phase proteins including ferritin, procalcitonin and c‐reactive protein, indicating systemic inflammation 29 .…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The mother presented with classic COVID‐19 symptoms including fever and a dry cough, 26 but abdominal pain and reduced fetal movements were also reported. Similar to previous reports, we observed that the clinical condition of the mother improved rapidly after delivery 27,28 . The mother also presented with elevated concentrations of several acute phase proteins including ferritin, procalcitonin and c‐reactive protein, indicating systemic inflammation 29 .…”
Section: Discussionsupporting
confidence: 88%
“…Similar to previous reports, we observed that the clinical condition of the mother improved rapidly after delivery. 27,28 The mother also presented with elevated concentrations of several acute phase proteins including ferritin, procalcitonin and c-reactive protein, indicating systemic inflammation. 29 In addition, at the time of delivery, SARS-CoV-2 RNA was found in the maternal blood and RT qPCR indicated the highest viral load within the placenta.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previous reports, we observed that the clinical condition of the mother improved rapidly after delivery 24,25 . Blood tests taken from the mother on the day of delivery revealed discreet liver injury.…”
Section: Discussionsupporting
confidence: 91%
“…8 Inducing early delivery to improve maternal health has precedent in SARS-CoV-2 infection as there has been a case report of a patient with deranged liver function whose biochemical abnormalities improved once she had delivered. 17 Currently the data are showing that the risks of SARS-CoV-2 infection in those who are pregnant are increased in comparison with those in the general population, as pregnant individuals with infection have increased rates of admission to intensive care units and are more prone to preterm birth. These preterm deliveries in these cases are cited to be due to iatrogenic intervention.…”
Section: Discussionmentioning
confidence: 99%